Do Vitamin D Levels Affect Bone Mineral Density in Reproductive Women with Low Ferritin Levels? - Hatice Hamarat; Göknur Yorulmaz; Ayşe Ekim Aydemir; Emel Örge Gönüllü; Ahmet Musmul; Sinem Gürcü (Galenos Yayinevi, 2022)
Objective:Iron deficiency anemia (IDA) is common in reproductive women. 25-hydroxyvitamin D [25-(OH)D] deficiency is common in those with IDA. The study evaluated the effect of low ferritin on 25-(OH)D levels and bone mineral density (BMD).Materials and Methods:One hundred forty women (15-25 years, 25-35 years, 35-45 years, 3 groups) with ferritin level <15 ng/mL and a control group of 50 healthy women were included in the study. A vitamin D level of 25-(OH)D>30.0 ng/mL was sufficient, vitamin D deficiency was defined as 25-(OH)D≥20.0, <30.0 ng/mL. Vitamin D deficiency as 25-(OH)D<20 ng/mL. Severe vitamin D deficiency 25-(OH)D<10 ng/mL. Femoral neck and lumbar spine BMD were measured by dual-energy X-ray absorptiometry. For the diagnosis of BMD, a Z-score of <-2 was evaluated with "lower bone mineral density than expected" and "expected bone density for >-2 years of age."Results:The mean ages of the patients and healthy controls were 34±10 and 29±9 years. Serum 25-(OH)D level was found to be low in the patient group (p<0.01). Low-intensity BMD was present in the low ferritin groups (p>0.05).Conclusion:Low vitamin D levels detected in reproductive women with anemia cause low BMD.